Bahudha and the Post 9/11 World - Singh, Balmiki Prasad (New Delhi, 2008)
The rise of terrorism and fundamentalism in recent times has brought about phenomenal changes in global politics. These unprecedented challenges call for a new, bold, and imaginative statecraft from world leaders. Underlining the need to transcend age-old peace mechanisms and reconstruct our language of discourse, this book propounds the concept of Bahudh"a-an eternal reality or continuum, a dialogue of harmony, and peaceful living. Bahudh"a recognizes the distinction between plural societies and pluralism, facilitates exchange of views, and promotes understanding of the collective good. The book is divided into five parts. The first part discusses the major events witnessed by the world during 1989-2001-the fall of Berlin Wall, transfer of Hong Kong to China, and the terrorist attack on the USA on September 11- and their implications for various nations, cultures, and international peace. The next part discusses India's experiences in handling the pluralistic challenge by citing examples from the Vedas and Puranas and analysing policies followed by Ashoka, Kabir, Guru Nanak, Akbar, and Mahatma Gandhi. In the subsequent sections, the author underlines the importance of Bahudh"a as an instrument of public policy for harmony and also discusses the global imperatives of following such an approach. He highlights the central role of education and religion in the building of a harmonious society and advocates the strengthening of the United Nations to become an effective global conflict resolution mechanism. B.P. Singh argues that the answer to terrorism lies in respecting human rights and appreciating various cultures and value systems. This is crucial for facilitating and enhancing dialogue processes eventually leading to amity and a peaceful world.
Keywords: Communal Harmony